Alliance Portfolio Management: Dimensions and Performance. Issue 2 (13th March 2015) - Castro, Ignacio; Roldán, José L.
<x xml:space="preserve">Abstract</x> Our paper contributes to the understanding of the alliance portfolio management capability by examining the relationships among their different dimensions and their impact on the alliance portfolio performance. The current study proposes and tests a multiple mediating model and tests the mediation. A variance‐based structural equation modelling (partial least squares) has been applied to a sample made up of 144 top Spanish companies. Our analysis on the one hand fosters the importance of the partnering proactiveness and their influences on the alliance portfolio performance, and, on the other, formulates mediation hypotheses, which posit how the relational governance and portfolio coordination dimensions play a critical mediating role in the partnering proactiveness – the alliance portfolio performance link. Results from the data analysis show that the dimensions of alliance portfolio management capability are related in such a way that the relational governance and the portfolio coordination: (1) partially mediate the effect of partnering proactiveness on the alliance portfolio value; and (2) exert significant influences on the alliance portfolio performance.